Exploring e-service quality through students' experience of Massive Open Online Courses (MOOC) / Safwana Nur Widad Safri, Zurinawati Mohi and Mohd Hafiz Hanafiah - Safri, Safwana Nur Widad; Mohi, Zurinawati; Hanafiah, Mohd Hafiz (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
This article identifies the primary dimensions and sub-dimensions of e-learning service quality for Massive Open Online Courses (MOOC). Sixteen undergraduate students who have experience learning through MOOCs are interviewed. All participants have completed at least three MOOC courses through the OpenLearning platform. The interviews reveal four primary dimensions and seven subdimensions: physical environment quality (convenience, platform appearance, and security), interaction quality (student-instructor interaction and student-student interaction), learning quality (teaching material and assessment), and lastly, the learning outcome quality. Instructors and MOOC platforms could target the findings to motivate students to finish MOOCs. The study also highlights MOOCs' weaknesses that instructors and OpenLearning need to note in order to improve their MOOCs.